China in the world economy: dynamic correlation analysis of business cycles - Jarko Fidrmuc; Iikka Korhonen; Ivana Bátorová (Bank of Finland, Institute for Economies in Transition (BOFIT), 2008)
We analyze the business cycles in China and in selected OECD countries between 1992 and 2006 using dynamic correlations. Nearly all OECD countries showpositive correlations of the very short-run developments which may correspond to intensive supplier linkages. However, dynamic correlations at the business cycle frequencies are negative. Countries facing a comparably longer history of intensive trading links tend to show slightly higher correlations of business cycles with China. Even though trade and financial flows do not really increase correlations of business cycles between China and OECD countries, they lower the degree of business cycle synchronization within the OECD area.
URN:NBN:fi:bof-201408071932
Keywords: E32; F15; F41; 330; Business cycles; synchronization; trade; FDI; dynamic correlation